الكفاءة النوعية لطلبة الدراسات العليا في التخصصات التربوية والنفسية في كليات مدينة بغداد (Journal Of Educational and Psychological Researches, 2013)
This thesis aims at identifying:• The level of qualitative efficiency of higher studies students in educational and psychological fields in the colleges of education Baghdad according to the perspectives of both teachers and students. • The statistical differences in levels of qualitative efficiency of higher studies students in educational and psychological fields in the colleges of education in  Baghdad Collegeteacher's viewpoints with reference to the two variables of the scientific title and gender.• The statistical differences in levels of qualitative efficiency of higher  studies students in the educational and psychological fields in the colleges of education in Baghdad from the perspective of higher studies students with reference to the two variables of the educational level and gender.The research came up with the following results:1-The students of studied specialties have got a certain level of qualitative efficiency according to perspectives of the two research samples, teachers and students' samples.2-The absence of having any significant differences having statistical denotations in the qualitative efficiency  for the teachers' sample is justified to be due to the variables of the scientific title and gender.3-Having differences with statistical significance in the level of qualitative efficiency  for the students' sample is justified to be due to the variable of the educational level for the MA students.